2010
DOI: 10.1177/1470320309358108
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 receptor blockade induces upregulation of renin-angiotensin-aldosterone system expression in terms of blood pressure regulation

Abstract: Objective.To compare the level of expression of the renin-angiotensin-aldosterone system (RAAS) in mice with or without the endothelin-1 receptor antagonist bosentan and to examine the potential value in blood pressure regulation. Materials and methods. Bosentan (10 mg/kg/d) and placebo were given to two groups of male C57BL/6 mice (n=5) from ages 6 to 12 weeks. The mRNAs of liver, kidney and lung were isolated for Northern blot analysis. A further 15 male C57BL/6 mice were divided into three groups (n=5): mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…ET-1 was first isolated from porcine aortic endothelial cells by Yanagisawa et al 24 Since its discovery, ET-1 has been demonstrated as one of the most potent known vasoconstrictors. 25 ET-1 release causes massive vasoconstriction, increased blood pressure and, in turn, induced endothelial dysfunction. ET-1 is synthesized by endothelial cells and smooth muscle cells, as well as by macrophages, cardiomyocytes, neurons, and renal medulla cells.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 was first isolated from porcine aortic endothelial cells by Yanagisawa et al 24 Since its discovery, ET-1 has been demonstrated as one of the most potent known vasoconstrictors. 25 ET-1 release causes massive vasoconstriction, increased blood pressure and, in turn, induced endothelial dysfunction. ET-1 is synthesized by endothelial cells and smooth muscle cells, as well as by macrophages, cardiomyocytes, neurons, and renal medulla cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that the diabetic complications are partly consequences of an activated ET system, which could lead to myocardial and vascular dysfunction. 16 Unfortunately, few study attempts to clarify the potent protective effect of bosentan, a non-selective ETa and ETb receptor antagonist, 17 on diabetic cardiovascular complications, especially myocardial fibrosis. There has been increasing research interest in understanding the impact of diabetes on cardiovascular disease, 18,19 and myocardial fibrosis is identified as an incurable complication.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HSH may have inhibited angiotensin II (Ang II), which stimulates ET secretion from cultured bovine endothelial cells via a receptor-mediated process [14][15][16]. Moreover, HSH may have enhanced ANP secretion, which interacts with ET secretion from the endothelium through the renin-angiotensin system [17,18]. Compared with Ringer-Locke liquor, HSH40, which inhibits ET secretion, may improve the symptoms of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%